2022
DOI: 10.3390/ani12030316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis C-3102 Spores as a Probiotic Feed Supplement on Growth Performance, Nutrient Digestibility, Diarrhea Score, Intestinal Microbiota, and Excreta Odor Contents in Weanling Piglets

Abstract: It has been well-documented that the dietary supplementation of Bacillus subtilis could improve piglet performance. The present study was conducted to investigate the effect of Bacillus subtilis C-3102 spores as a probiotic feed supplement on growth performance, nutrient digestibility, fecal score, intestinal microbiota, and excreta odor contents in weanling piglets. A total of 150 crossed ((Yorkshire × Landrace) × Duroc) weanling piglets (28-days-old), with an average initial body weight of 7.53 ± 1.23 kg, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 45 publications
(53 reference statements)
0
5
1
Order By: Relevance
“…Energy and dry matter are also parameters that may vary depending on the study. Here, again, results differ between already-published studies [ 65 , 66 ]. The results from our study suggest that little to no increase in digestibility was achieved from the probiotic action.…”
Section: Discussioncontrasting
confidence: 99%
“…Energy and dry matter are also parameters that may vary depending on the study. Here, again, results differ between already-published studies [ 65 , 66 ]. The results from our study suggest that little to no increase in digestibility was achieved from the probiotic action.…”
Section: Discussioncontrasting
confidence: 99%
“…The latter authors also commended the microbial agent for reducing pH, NH 3 concentration, and urease activity, which are part of emission factors. Kim et al (2005) A recent publication by Hu and Kim (2022) found that dietary B. subtilis supplementation in weaning piglets had a significant effect on R-SH emissions, but not on NH 3 and H 2 S levels. In contrast, our results in Exp.…”
Section: Discussionmentioning
confidence: 99%
“…The use of probiotic supplementation strategies in dogs is ever-increasing, with the most common being Lactobacillus , Bifidobacterium and Enterococcus strains. However, there is increasing interest in the use of Bacillus species as probiotics since their spore-forming ability favors their survival in the acidic gastric environment over other probiotic species [ 1 , 2 , 3 , 4 , 5 ]. The subsequent germination of B. subtilis to their vegetative form allows for the growth of the probiotic bacteria in the small intestine and is believed to increase their beneficial effect on the host [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other B. subtilis strains have also previously been shown to have beneficial effects on digestive health and the immune system in humans and production animals [ 1 , 2 , 3 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], however, no studies have so far investigated its effects on the microbiome or metabolome in healthy dogs. This is critically needed to prove the safety of a probiotic strain in a novel species before further clinical testing in animals with gastrointestinal distress is performed.…”
Section: Introductionmentioning
confidence: 99%